HUBUNGAN PENDAMPINGAN IBU KEPADA ANAK DALAM PENGGUNAAN GADGET DENGAN KESEHATAN MENTAL ANAK USIA DINI (4-6) TAHUN DI TK AISYIYAH BUSTANULATHFAL IV SEMBORO-JEMBER - Wahyuni, Ninik Sri; Sari, Yesi Nur Endah; Lestari, Dwi Anggun (NHM PRESS, 2024)
Children who are mentally healthy at an early age mean that they have reached optimal developmental stages, mastered healthy social skills, and are able to deal with the problems they face well. The purpose of this study was to determine the correlation between mother's assistance to children in using gadgets and children's mental health Early. This study examines the correlation between mother's guidance in children's gadget use and the mental health of early childhood (ages 4-6) at Aisyiyah Bustanulathfal IV kindergartens Semboro- Jember. The research adopts a correlational design with a cross-sectional approach. The population consisted of 41 children aged 4-6 years in Aisyiyah Bustanulathfal IV kindergartens. Thel sampling used the total sampling technique. Data was collected using a data collection sheet and analyzed using SPSS, applying exact fisher test with a significance level of α<0.05. Results indicated a majority of respondents, 34 (83%), are observed to have healthy mental health while using gadgets, whereas 7 (17%) respondents are observed to have good mental health but without supervision. Based on the analysis, there is no significant correlation found between mother's guidance in children's gadget use and the mental health of early childhood (ages 4-6) at Aisyiyah Bustanulathfal IV kindergartens Semboro-Jember with (Exact Sig. (1-sided)= 0.512 (α>0.05).